PENGEMBANGAN BUTIR SOAL MATEMATIKA BERBASIS QUIZIZZ (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study designed a numeracy test instrument using the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The analysis stage involved gathering and reviewing needs as the basis for product development. The design stage focused on developing the initial draft. The development stage then included expert assessment and small-group trials. The product was then implemented in a broader implementation stage, with an evaluation stage reviewing each step to ensure product quality. Validation results showed that the instrument received a “very valid” category from the media and materials validators, with an average score of 4.5 and a percentage of 91%. The language validator gave an average score of 3.7, categorized as “valid.” In terms of practicality, teachers gave an average score of 5, categorized as “very practical,” and students in both small and large trials also responded as “very practical.” Therefore, the Quizizz-based numeracy instrument was declared valid, practical, and feasible to implement.